2011
DOI: 10.4028/www.scientific.net/msf.695.49
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Bi<sub>0.5</sub>Na<sub>0.5</sub>ZrO<sub>3</sub> Powder by Mixed Oxide Method

Abstract: Lead-free bismuth sodium zirconate powder with formula Na0.5Bi0.5ZrO3 was prepared by conventional mixed oxide method. Bismuth sodium zirconate (BNZ) powder with 10wt%Na2CO3 was calcined at 800 °C for 2 h dwell time. Investigation of the effects of re-calcination and dwell time on phase formation of powders was also carried out. The results revealed that re-calcination significantly affected the formation of single-phase BNZ powder. Phase characteristics were checked by X-ray diffraction (XRD). Powder Cell sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…In the ceramic without Ti addition, XRD pattern showed that BNZ ceramic possessed orthorhombic perovskite phase, in good agreement with previously reported result [2,4]. With increasing substitution, shift of diffraction pattern toward a higher reflection angle was seen due to the fact that smaller Ti 4+ ions (0.605 Å) [8] substituted larger Zr 4+ ions (0.72 Å) [8] in the lattice and then reduced the unit cell volume.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In the ceramic without Ti addition, XRD pattern showed that BNZ ceramic possessed orthorhombic perovskite phase, in good agreement with previously reported result [2,4]. With increasing substitution, shift of diffraction pattern toward a higher reflection angle was seen due to the fact that smaller Ti 4+ ions (0.605 Å) [8] substituted larger Zr 4+ ions (0.72 Å) [8] in the lattice and then reduced the unit cell volume.…”
Section: Resultssupporting
confidence: 89%
“…The phases were divided into three regions, the single orthorhombic phase region up to x = 0.2 mol fraction, a two-phase region at x = 0.3 and 0.4 mol fraction in which (321) orthorhombic and (300) rhombohedral peaks overlapped to cause the left side intensity (blue peak) to become higher than a right side (123 peak), then a single rhombohedral phase region beyond x = 0.5 mole fraction. The quantitative data of lattice parameters for BNZT having x = 0, 0.1, 0.2, 0.5 and 0.6 The data are taken from previous report [2]. b The data are taken from previous report [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unit cell of x BNZ ( x = 0–0.10) was refined using the tetragonal P 4 mm symmetry, in accordance with what is reported for BKT . The diffractograms were refined using cubic Pm true3false¯ m unit cell for x BNZ ( x = 0.15–0.80), while BNZ ( x = 1) was refined using the orthorhombic Pnma unit cell . At high BKT content no secondary phases could be observed by XRD, but from x = 0.2 traces of secondary phases could be observed.…”
Section: Resultsmentioning
confidence: 99%
“…A transition from rhombohedral to orthorhombic structure has been observed for BNT upon 58–60 mol% substitution of Zr for Ti . The crystal structure of Bi 0.5 Na 0.5 ZrO 3 (BNZ) has been reported to be orthorhombic Pnma …”
Section: Introductionmentioning
confidence: 99%